STRATEGI PELAYANAN MISI DAVID LIVINGTONE DAN IMPLEMENTASINYA BAGI PELAYAN MISI ERA SOCIETY 5.0 - Yolanda Caroline Christian; Gresya Widia Evani Aritonang; Pasaribu, Ferdinan (Jurnal Matetes STT Ebenhaezer, 2023)
David Livingstone's missionary strategy. This article reviews one of the missionary figures from several missionaries, namely David Livingtone. David Livingstone is one of the missionary figures who has a vision for Africa, where in the mission David Livingtsone always pays attention to things that become field needs, as a strategy in mission according to place and circumstances, as well as time, one of which is as a missionary who has medical expertise. Just like David Livingstone, today's evangelists will also be faced with various forms of field needs in mission, one of which is the needs of the times. Where the progress of the times continues to develop until the era of society 5.0. In the era of Society 5.0 which is characterized by progress in various aspects that are so fast and dynamic, including advances in digital technology. The era of Society 5.0 is also included in the category of the PostModern period, which is characterized by the development of information and communication technology. The problem is that not all theological schools and mission agencies pay attention to future needs in mission, including digital needs in the era of Society 5.0. The method in this research is a qualitative method with a biographical approach. David Livingtone's biographical approach to mission with three things that are field needs is summarized later into David Livingtone's mission service strategy, namely:civilization, commerce, and Christianity will then be drawn into the implementation for today's missionaries in facing the era of society 5.0.